Melt pond distribution and geometry in high Arctic sea ice derived from aerial investigations. Issue 73 (9th September 2016) - Huang, W.; Lu, P.; Lei, R.; Xie, H.; Li, Z.
ABSTRACT: Aerial photography was conducted in the high Arctic Ocean during a Chinese research expedition in summer 2010. By partitioning the images into three distinct surface categories (sea ice/snow, water and melt ponds), the areal fraction of each category, ice concentration and the size and geometry of individual melt ponds, are determined with high-spatial resolution. The ice concentration and melt pond coverage have large spatial deviations between flights and even between images from the marginal ice zone to the pack ice zone in the central Arctic. Ice concentration and pond coverage over high Arctic (from 84°N to north) was 75% and 6.8%, respectively, providing 'ground truth' for the unusual transpolar reduction strip of ice indicated concurrently by AMSR-E data and for the regions (north of 88°N) where no passive microwave sensors can cover. Melt pond size and shape distributions are examined in terms of pond area ( S ), perimeter ( P ), mean caliper dimension (MCD) ( L ), roundness ( R ), convex degree ( C ), the ratio of P / S and fractal dimension ( D ). Power-law relationships are developed between pond size and number. Some general trends in geometric metrics are identified as a function of pond area including R, C, P / S and D . The scale separation of pond complexity is demonstrated by analyzing area-perimeter data. The results will potentially help the modelling of melt pond evolution and the determination of heterogeneity of under-ice transmitted light fields.